2018
DOI: 10.1016/j.ijfoodmicro.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli is the predominant diarrheagenic E. coli pathotype among irrigation water and food sources in South Africa

Abstract: Diarrheagenic E. coli (DEC) has been implicated in foodborne outbreaks worldwide and have been associated with childhood stunting in the absence of diarrhoea. Infection is extraordinarily common, but the routes of transmission have not been determined. Therefore, determining the most prevalent pathotypes in food and environmental sources may help provide better guidance to various stakeholders in ensuring food safety and public health and advancing understanding of the epidemiology of enteric disease. We chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
3
25
2
2
Order By: Relevance
“…This correlates well with studies conducted outside the African content [56,57]. In contrast, similar studies carried out in sub-Saharan Africa (Tanzania, South Africa and Mozambique) reported EAEC as the most prevalent DEC pathotype [58][59][60][61][62] yet it was not detected in this study. As expected, DEC were predominantly isolated from Anal/fecal swabs.…”
Section: Extraintestinal Pathogenic Escherichia Coli (Expec)supporting
confidence: 87%
“…This correlates well with studies conducted outside the African content [56,57]. In contrast, similar studies carried out in sub-Saharan Africa (Tanzania, South Africa and Mozambique) reported EAEC as the most prevalent DEC pathotype [58][59][60][61][62] yet it was not detected in this study. As expected, DEC were predominantly isolated from Anal/fecal swabs.…”
Section: Extraintestinal Pathogenic Escherichia Coli (Expec)supporting
confidence: 87%
“…This correlates well with studies conducted outside the African content[51,52]. In contrast, similar studies carried out in sub-Saharan Africa (Tanzania, South Africa and Mozambique) reported EAEC as the most prevalent DEC pathotype[53][54][55][56][57] yet it was not detected in this study. As expected, DEC were predominantly isolated from Anal/fecal swabs.…”
supporting
confidence: 87%
“…Members of this family, that is, Escherichia coli and Salmonella spp., have often been associated with foodborne bacterial outbreaks following raw fresh produce consumption (Tope, Hitter, & Patel, 2016). This includes diarrheagenic E. coli strains, including enteropathogenic (EPEC), enterotoxigenic (ETEC), enterohaemorrhagic (EHEC), enteroaggregative (EAEC), and enteroinvasive (EIEC) E. coli in foodborne disease outbreaks (Aijuka, Santiago, Girón, Nataro, & Buys, 2018; Canizalez‐Roman et al., 2019). In addition to generic E. coli , diarrheagenic strains are also found in the intestinal tracts of mammals and are therefore often used as indicators of fecal contamination in fresh produce supply chains (Denis et al., 2016).…”
Section: Introductionmentioning
confidence: 99%